2013
DOI: 10.1093/qjmed/hct222
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and chronic kidney disease on secondary prevention post-primary percutaneous coronary intervention

Abstract: The uptake of secondary prevention medication is high following PPCI in the UK, even in the elderly and in those with renal dysfunction. A focus on strategies to improve up-titration and continuation of drugs following discharge is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…These findings were independent of a number of clinical variables that might impact on use of these drugs, including history of hypertension, diabetes and age. A similar trend of higher use of ARBs following PCI for ST-elevation MI was seen in patients with severe CKD in a recently published UK study [14]. Guidelines relating to the management of patients with CKD do not differentiate between the use of ACE inhibitors or ARBs [20].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These findings were independent of a number of clinical variables that might impact on use of these drugs, including history of hypertension, diabetes and age. A similar trend of higher use of ARBs following PCI for ST-elevation MI was seen in patients with severe CKD in a recently published UK study [14]. Guidelines relating to the management of patients with CKD do not differentiate between the use of ACE inhibitors or ARBs [20].…”
Section: Discussionmentioning
confidence: 71%
“…The latter figure is perhaps more relevant, since the mean age of subjects in our study was 64 years. A recent study of consecutive patients receiving primary PCI for myocardial infarction in the UK demonstrated a mean age of approximately 64 years, with 17.6% exhibiting CKD stages 3–5 [14]. In the Canadian study [13], the prevalence of comorbidities such as hypertension and diabetes mellitus was greater in those with CKD, but no real difference in lipid profile (excepting triglycerides) was seen.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, although the age group > 65 years had the highest accumulation of cardiovascular co-morbidities, only half of them were prescribed RAS inhibitor. This is perhaps due to the adverse events associated with these medications and the suboptimal use of secondary preventive measures in this age group described in literature [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This inverse relationship between ESKD and death is consistent with previous studies [ 8 , 25 28 ]. For example, O’Hare et al in a study of 209,622 patients aged 18–100 years with CKD stages 3 to 5, showed this inverse relationship between death and ESKD [ 24 ]. In this study the adjusted HR (95% CI) for death in the age group 75–84 years, for CKD stages 3b, 4 and 5 was 2.6 (1.8–3.7), 3.1 (1.9–5.1) and 4.4 (1.6–22.7) respectively, compared to the reference group, of patients aged 18 to 44 years.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zachariah et al . () showed that people aged >75 years of age received fewer secondary preventive measures compared with younger subjects on discharge, following a percutaneous coronary intervention (PCI) (p < 0.01 for beta blocker, ACE‐i/ARB and statin). Amongst people with eGFR <60 ml/min/1.73 m 2 , only 83.5% received either an ACE‐I or ARB at discharge.…”
Section: Influence Of Medications Upon Cardiovascular and Renal Outcomentioning
confidence: 99%